Brands versus cultivar denomination in two brazilian geographical indications for coffee - Barbosa, Patrícia Maria da Silva; Lage, Celso Luiz Salgueiro; Fernandes, Lucia Regina Rangel de Moraes Valente (Coffee Science - ISSN 1984-3909, 2016)
The coffees consumer interest based on quality and origin labeling increasing is creating a market which seeks for more than can be perceived through the five physical senses. These extra attributes can be signaled by the producers through the use of brands and geographical indications. Insert in a coffee package the cultivars denomination as a brand could be a way of carrying the prestige of it to the product. However, registers a cultivar denomination as trademark is prohibited under the Brazilian Plant Cultivar Protection Act. This study sought to identify the existence of brands with varieties denominations used by “Região do Cerrado Mineiro” and “Alta Mogiana”, coffee Brazilian Geographic Indications.As well discuss conflicts legislative possible solutions. It has confronted information provided by Ministry of Agriculture, Livestock and Food Supply´s and National Institute of Industrial Property´ databases. 7 of the 10 cultivars discriminated on Geographical Indications are present in brands deposited at the National Institute of Industrial Property. But none of the registers belongs to the National Listrecord designation´s owner. It´s suggested that varieties denominations should use VI, X and XVII Industrial Property Law ´s sections of prohibitions, as applicable.